SIMULATORS FOR TRAINING OF ROV OPERATOR - B. I. Shakhtarin; V. V. Weltishev (Научный вестник МГТУ ГА)
In the article issues of the organization of imitating modeling complexes for training operators of Remotely Operated Underwater Vehicle are considered. It is reported about practical development of sea exercise simulation in Bauman MSTU.